Genome-wide genotyping uncovers genetic profiles and history of the Russian cattle breeds. (February 2018) - Yurchenko, Andrey; Yudin, Nikolay; Aitnazarov, Ruslan; Plyusnina, Alexandra; Brukhin, Vladimir; Soloshenko, Vladimir; Lhasaranov, Bulat; Popov, Ruslan; Paronyan, Ivan; Plemyashov, Kirill; Larkin, Denis M.
Abstract One of the most economically important areas within the Russian agricultural sector is dairy and beef cattle farming contributing about 11 billion to the Russian economy annually. Trade connections, selection and breeding have resulted in the establishment of a number of breeds that are presumably adapted to local climatic conditions. Little however is known about the ancestry and history of Russian native cattle. To address this question, we genotyped 274 individuals from 18 breeds bred in Russia and compared them to 135 additional breeds from around the world that had been genotyped previously. Our results suggest a shared ancestry between most of the Russian cattle and European taurine breeds, apart from a few breeds that shared ancestry with the Asian taurines. The Yakut cattle, belonging to the latter group, was found to be the most diverged breed in the whole combined dataset according to structure results. Haplotype sharing further suggests that the Russian cattle can be divided into four major clusters reflecting ancestral relations with other breeds. Herein, we therefore shed light on to the history of Russian cattle and identified closely related breeds to those from Russia. Our results will facilitate future research on detecting signatures of selection in cattle genomes and eventually inform future genetics-assisted livestock breeding programs in Russia and in other countries.